The impact of smart input subsidy program on farm productivity: Evidence from Tanzania - Rehema Karata (Scientific African, 2024)
Policymakers have a renewed interest in input subsidy programs in sub-Saharan Africa. However, the evidence of the program's impact is mixed. This paper uses the case of Tanzania's National Agricultural Input Voucher Scheme (NAIVS) to examine its effect on farm productivity. To account for the endogeneity problem arising from the non-random targeting of beneficiaries, this study employed a staggered difference-in-differences approach with a double robust estimator method on a three-wave panel survey. This approach is relevant because the treatment variable—NAIVS participation was gradually rolled out to households over multiple periods and groups. The results do not show evidence that the NAIVS program increased farm productivity. However, the group aggregate effects suggest that the group initially treated in 2010 experienced a positive and significant impact on maize production and income. This could indicate that during the early stages of the NAIVS program, extra effort was likely invested to ensure its effectiveness. Furthermore, the heterogeneous effect of farm size reveals that the NAIVS program increased the participation of beneficiary households with large-scale farms rather than small-scale farms. This suggests that the program did not effectively target resource-poor households. Finally, this paper calls for effective targeting and careful implementation of programs to improve farmer productivity.